Emerging affinities : possible futures of performative arts - Borowski, Mateusz; Chaberski, Mateusz; Sugiera, Malgorzata (Theater (Transcript (Firm)) ;, 2019)
This volume is a response to the growing need for new methodological approaches to the rapidly changing landscape of new forms of performative practices. The authors address a host of contemporary phenomena situated at the crossroads between science and fiction which employ various media and merge live participation with mediated hybrid experiences at both affective and cognitive level. All essays collected here move across disciplinary divisions in order to provide an account of these new tendencies, thus providing food for thought for a wide readership ranging from performative studies to the social sciences, philosophy and cultural studies.